PENGARUH ATRIBUT PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH SIMPEDES PADA BRI UNIT KANTOR CABANG PALU - Harun, Rustam H. (Katalogis, 2015)
The purpose of this research are :1) to analyze the influence of product attributes on customers SIMPEDES’ satisfaction at BRI Branch Office Palu; 2) to analyze the influence of service quality on customers SIMPEDES’ satisfaction at BRI Branch Office Palu; 3) to analyze the influence of customers’ satisfaction on customer SIMPEDES’ loyalty at BRI Branch Office Palu; 4) to analyze the influence of service quality on customers SIMPEDES’ loyalty at BRI Branch Office Palu; 5) to analyze the influence of customers’ satisfaction on customers SIMPEDES’loyalty at BRI Branch Office Palu. The sample consists of 200 respondents who serve as customers of SIMPEDES BRI Branch Office of Palu and method of analysis is Stuctural Equation Modeling (SEM). The results indicate that: 1).product attributes has significant influence on customers’ satisfaction; 2.) service quality has significant influence on customers’ satisfaction; 3) product attributes has insignificant influence on customers’ loyalty; 4) service quality has insignificant influence on customers’ loyalty; 5) customers’ satisfaction has significant influence on their loyalty.